PELATIHAN PEMBUATAN PROBIOTIK HERBAL BAGI KELOMPOK PEMBUDIDAYA IKAN - Hayati Soeprapto; Heri Ariadi; Kharismatul Khasanah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The use of probiotics with herbal ingredients is considered to provide many benefits for fish farming activities. The purpose of this community service activity is to educate aquaculturist about the procedures for making and using herbal probiotics for aquaculture activities. The method used in the implementation of this community service activity is counseling and training activities related to the manufacture of herbal probiotics and their application to feed, then mentoring activities are also carried out. This activity was attended by 12 fish farmers in Jeruksari Village, Pekalongan Regency. The results of this community service activity show the potential for aquaculture in Jeruksari Village is quite promising to be developed. In addition, during the service activities, the aquaculturist were also very active in participating in activities starting from the presentation of the manufacture and function of herbal probiotics during the counseling session to when the tutorial on making herbal probiotics was conducted. In addition, participants also feel benefited by the knowledge transfer that they can apply in their daily activities. The conclusion that can be drawn from the implementation of this community service activity is that in general the service activities regarding the training of making herbal probiotics are going very well and in accordance with the target of the program. Participants said that this kind of program activity was considered to provide a lot of knowledge and benefits for them